The evidence supporting single-use intermittent catheters in people with spinal cord injury - New, Peter Wayne (Spinal Cord Ser Cases, 2020)
Intermittent catheterization (IMC) is the accepted evidence-based best practice for bladder management in people with voiding dysfunction due to neurogenic bladder. The two methods for performing IMC over the decades since this practice was introduced are reuse and single-use catheters. There are perceived advantages and disadvantages of each method of performing IMC. There is considerable evidence that single-use IMC is associated with better health outcomes, including reduced risk of urinary tract infection, urethral trauma, and quality of life. People performing IMC also indicate a preference for single-use, although there are advantages of reuse that need to be acknowledged. Ideally, further research is needed in this area, particularly around the washing and storage of reuse catheters, as well as an adequately powered multicenter RCT comparing reuse with single-use IMC, but there are numerous challenges associated with progressing this research.